Mapping of Crime-Prone Areas in The Ulu Area of Palembang City Based on Public Service Availability Factors - Yauni, Rosada Nur Chusna (PPSDP International Journal of Education, 2024)
Crimes often occur in various places in Palembang City; the Ulu area is the most dominant area, especially the Seberang Ulu I District. Different places and times make it difficult to determine which areas have the highest level of crime vulnerability. This information is needed by the public and law enforcement. Most of the crimes that arise are caused by economic influences. This study tries to link two variables, namely the crime rate variable and the variable availability of public services. The method used is descriptive-quantitative with spatial analysis. Conclusions in this study: (1) Several areas in Seberang Ulu I District have different levels of vulnerability to crime. Areas that are categorized as prone to crime are areas that have public services, including Tuan Kentang, 7 Ulu, and 15 Ulu. (2) Crimes most often occur at night between 18.00 and 05.59 WIB, with as many as 19 cases, and in the afternoon between 06.00 and 17.59 WIB, with as many as 11 cases.